The Zinc Nutritional Immunity of Epinephelus coioides Contributes to the Importance of znuC During Pseudomonas plecoglossicida Infection - Huang, Lixing; Zuo, Yanfei; Qin, Yingxue; Zhao, Lingmin; Lin, Mao; Yan, Qingpi (Frontiers in Immunology, 2021)
Previously, the dual RNA-seq was carried out in a Pseudomonas plecoglossicida- Epinephelus coioides infection model to investigate the dynamics of pathogen-host interplay in vivo. ZnuC, a member of ZnuCBA Zn importer, was found transcriptionally up-regulated during infection. Thus, this study aimed to assess its role during the trade-off for Zn between host and P. plecoglossicida. ICP-MS analysis and fluorescent staining showed that Zn was withheld from serum and accumulated in the spleen, with increased Zn uptake in the Golgi apparatus of macrophages after infection. Additionally, growth assay, macrophage infection and animal infection after gene knockout/silencing revealed that znuC was necessary for growth in Zn-limiting conditions, colonization, intracellular viability, immune escape and virulence of P. plecoglossicida. Further analysis with dual RNA-seq revealed associations of host’s Zn nutritional immunity genes with bacterial Zn assimilation genes. IL6 and ZIP4 played key roles in this network, and markedly affected znuB expression, intracellular viability and immune escape, as revealed by gene silencing. Moreover, EMSA and GFP reporter gene analysis showed that Fur sensed changes in Fe concentration to regulate znuCBA in P. plecoglossicida. Jointly, these findings suggest a trade-off for Zn between host and P. plecoglossicida, while ZnuC is important for P. plecoglossicida Zn acquisition.